2017
DOI: 10.1024/0301-1526/a000611
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of cardiovascular risk factors among 28,000 employees

Abstract: We regard obesity as the number one cardiovascular risk which should be assessed by various medical, legislative, and socio-economic actions to limit future mortality and health-care costs in Germany.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
1
4
0
1
Order By: Relevance
“…Increasing BMI was associated with hypertension regardless of the threshold used to define it. In a 2017 study among 28,000 German employees, it was also found that obesity was associated with a four-times higher risk of hypertension (Scheerbaum et al, 2017). Similarly a systematic review of the determinants of hypertension among 34,919 workers in West Africa found that obesity was a significant predictor of hypertension (Bosu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing BMI was associated with hypertension regardless of the threshold used to define it. In a 2017 study among 28,000 German employees, it was also found that obesity was associated with a four-times higher risk of hypertension (Scheerbaum et al, 2017). Similarly a systematic review of the determinants of hypertension among 34,919 workers in West Africa found that obesity was a significant predictor of hypertension (Bosu, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity in the workforce is associated with difficulty performing work in confined spaces, decreased productivity, greater absenteeism, higher turnover and cost to company [61]. In addition, obesity has been associated with higher odds of hypertension among employees in developed [79] and developing countries [80,81]. The odds of hypertension were 2.3 times higher for employees with abdominal obesity (by WC) and 3.7 times higher for employees (by WHtR) in this study compared to employees with normal WC and WHtR.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that UA, lnTG, lnLp (a), and lnHCY were relatively independent and were used in subsequent logistic analysis; in the blood lipid spectrum, although lnTG has a wide correlation with other indicators, the correlation coefficient is < 0.5, so it was also included in the subsequent logistic analysis. HDL-C and LDL-C are common clinical indexes that serve as common risk factors for CHD, but their role in the prediction of CHD is still in dispute, 13 , 14 and needs to be confirmed by research analyses, so they were also included in the subsequent logistic analysis. Pearson correlation matrix analysis showed that LDL-C and lnAPOB100 have a strong correlation, and that HDL-C and APOA1 have a strong correlation; in order to ensure the reliability of the results analysis regarding HDL-C and LDL-C, APOA1 and lnAPOB100 were not included in the regression indexes.…”
Section: Discussionmentioning
confidence: 99%